PENGEMBANGAN MODUL IPS BERBASIS KONTEKSTUAL DENGAN MENGGUNAKAN MODEL COOVERATIVE LEARNING DI KELAS IV SD NEGERI MUARA KATI BARU II - Siti Nia Santia; Andri Valen; Abu Bakar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to produce a contextually based social studies module development using the cooperative learning model. This type of research is Research and Development with a 4-D development model. The subjects of this research were fourth grade students at SD Muara Kati Baru II. Data collection techniques use questionnaires, tests and documentation. Based on the validation results of the Contextually Based Social Sciences Module Using the Cooperative Learning Model based on the assessment of language, material and media experts, it shows that the Contextually Based Social Sciences Module Using the Cooperative Learning Model meets the valid criteria with an average score of 0.87. Meanwhile, from the analysis of teacher and student practicality sheet assessments, it was found that the Contextually Based Social Sciences Module Using the Cooperative Learning Model met the practical criteria with an average score of 89.16%. In the field test, an N-gain (g) of 0.75 was obtained with a high classification, which means that the Contextually Based Social Sciences Module Using the Cooperative Learning Model has high effectiveness. Based on the research results, it can be concluded that the Contextually Based Social Studies Module Using the Cooperative Learning Model is proven to be valid, practical and effective in social studies learning for fourth grade students at SD Muara Kati Baru II.